Lipid rafts in mast cell signaling - Dráber, Petr; Dráberová, Lubica (Molecular immunology, 2002)
Lipid rafts are defined as plasma membrane microdomains enriched with glycosphingolipids and cholesterol which render them insoluble in non-ionic detergents. Many surface receptors are constitutively or inducibly associated with lipid rafts, and it has been suggested that the rafts function as platforms regulating the induction of signaling pathways. The signaling capacity of lipid rafts has been extensively studied in rat basophilic leukemia cells. An aggregation of lipid raft components, such as glycosylphosphatidylinositol (GPI)-anchored glycoproteins (Thy-1 or TEC-21), triggers cell activation events which are similar to, but not identical with activation via the high-affinity IgE receptor (FcepsilonRI). Although FcepsilonRI in resting cells is not associated with lipid rafts, its aggregation induces a weak association with rafts and subsequent activation events. The properties of lipid rafts as well as the molecular mechanisms of their involvement in signal transduction are poorly understood. This review presents a critical analysis of recent results on structure-function relationship of lipid rafts and their regulatory role in signal transduction in mast cells.
Keywords: skupina kinas odvozených od src-genu; signální transdukce; Rats; receptory IgE; detergenty; Receptors, IgE; src-Family Kinases; mastocyty; Signal Transduction; Cholesterol; krysa rodu Rattus; Detergents; zvířata; membránové mikrodomény; Membrane Microdomains; antigeny Thy-1; Thy-1 Antigens; Mast Cells; cholesterol; Animals